PROBLEM BASED LEARNING (PBL) BERBASIS ETNOSAINS DAN ETNOMATEMATIK - Nadiyah; Mardiana; Wahyu Iskandar; Fia Alifah Putri (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2022)
This paper aims to see how PBL is integrated with ethnoscience and ethnomamatics. PBL as a contextual model of students often does not find a new direction in approach. This research introduces a new direction of PBL learning schemes through ethnoscience and ethnomamatics. Descriptive qualitative research of Cronin et al., (2008), namely (1) choosing a review topic, (2) finding and selecting appropriate articles, (3) analyzing and synthesizing literature, and 4) conducting a review of writing in a Mix with the development of Thiagarajan's definition. , design, development and dissemination. The results of this study (a) Ethnoscience-based PBL has three conceptual steps (1) A new conceptual framework that is a synergy between ethnoscience and PBL to improve contextuality and meaning in science learning, (2) Steps for developing ethnoscience-based learning, and 3) steps to integrate ethnoscience into PBL and how to apply it in science learning. (b) A PBL-based ethnomathematics approach may improve understanding of mathematics. The integration of teacher performance, student activities, and infrastructure utilization can improve understanding of mathematics based on ethnomathematics designed with a Four-D model (research design) which consists of (1) defining, (2) designing, (3) developing, and (4) spreading.